The use of Mudah CS2 in Home-Based Learning: A case study / Goh Kok Ming - Goh, Kok Ming (2021)
The widespread prevalence of COVID-19 pandemic has affected educators and parents alike. Due to the sudden closure of schools, students are missing social interaction which is vital for better learning and grooming while most schools have started online classes. This has become a tough routine for the parents working online at home since they have to ensure their children's education. Thus, parents and students faced problems in following the learning timetable, especially for those in the rural area. This smart application was developed to facilitate teachers, students and parents to attend online classes according to the PdPR 2.0 (Home-Based Learning) timetable based on MOE guidelines. This application was developed in the Android version which can be downloaded and installed in smartphones. Through this application, tutorial materials and notes can be accessed easily and systematically according to subjects. Besides, parents can monitor their children's learning progression and attendance easily. Addressing these contextual challenges, it fulfills the requirement gap for remote learning.